The pentester blueprint : starting a career as an ethical hacker - Wylie, Phillip L. (John Wiley, 2021)
The Pentester BluePrint: Your Guide to Being a Pentester offers readers a chance to delve deeply into the world of the ethical, or "white-hat" hacker. Accomplished pentester and author Phillip L. Wylie and cybersecurity researcher Kim Crawley walk you through the basic and advanced topics necessary to understand how to make a career out of finding vulnerabilities in systems, networks, and applications. You'll learn about the role of a penetration tester, what a pentest involves, and the prerequisite knowledge you'll need to start the educational journey of becoming a pentester. Discover how to develop a plan by assessing your current skillset and finding a starting place to begin growing your knowledge and skills. Finally, find out how to become employed as a pentester by using social media, networking strategies, and community involvement. Perfect for IT workers and entry-level information security professionals, The Pentester BluePrint also belongs on the bookshelves of anyone seeking to transition to the exciting and in-demand field of penetration testing. Written in a highly approachable and accessible style, The Pentester BluePrint avoids unnecessarily technical lingo in favor of concrete advice and practical strategies to help you get your start in pentesting. This book will teach you: -The foundations of pentesting, including basic IT skills like operating systems, networking, and security systems -The development of hacking skills and a hacker mindset -Where to find educational options, including college and university classes, security training providers, volunteer work, and self-study -Which certifications and degrees are most useful for gaining employment as a pentester -How to get experience in the pentesting field, including labs, CTFs, and bug bounties
Includes index.
Keywords: Penetration testing (Computer security) -- Vocational guidance.; Hacking -- Vocational guidance.; elektronické knihy; electronic books